Pengaruh Risiko Pembiayaan dan Likuiditas Terhadap Profitabilitas pada Perbankan Syariah di Bursa Efek Indonesia (Periode 2020-2024) - Nur azizah Azizah; Diah Yudhawati; Yudiana Yudiana (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to determine the effect of financing risk and liquidity on profitability, both partially and simultaneously. The population for this study consists of four Sharia Commercial Banks (BUS) listed on the Indonesia Stock Exchange (IDX). The variables include financing risk (proxied by Non-Performing Financing/NPF), liquidity (proxied by the Financing to Deposit Ratio/FDR), and profitability (proxied by Return on Assets/ROA). This study employs quantitative data, specifically secondary data obtained from the banking companies' published reports on the IDX. A purposive sampling method was used, resulting in the selection of four companies that met the criteria. The analysis techniques employed include descriptive statistical analysis, panel data regression, classical assumption testing, multiple linear regression, the coefficient of determination, and hypothesis testing using EViews 10 software. The results indicate that, when analyzed individually (partially), the financing risk variable has a significant effect on profitability, whereas liquidity does not. However, when analyzed simultaneously, both financing risk and liquidity have a significant effect on profitability.